Oyster Mussels (Crassostrea gigas) Transport System (Case Study in Kamashima Company) in Hyogo, Japan: English - Salim Ibrahim; Yuli Andriani (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2022)
Oyster culture is an aquaculture activity that is mostly carried out in Japanese waters. While in Indonesia, oyster shells are widely consumed, but they have not been produced through the culture process but are caught on the high seas. This study aims to determine how the application of technology and transportation in the culture and sale of oyster in Japan. Based on literature studies and activities at the Kamashima-Japan company, transportation is an important part of oyster farming activities. Oyster transportation technology is currently carried out in two areas, namely sea and land, using open and closed dry transportation methods. Sea transportation uses Hydraulic Cranes for Shipboard Use (Marine Cranes) technology which is applied to special vessels measuring 6-7 GT with the classification of Truck-mounted cranes, while land transportation uses Styrofoam boxes equipped with ice blocks to immobilize the temperature. The size of the wind that blows in the sea, the time of pick-up and delivery, and the number of oyster shells required are important factors in these transportation activities.